Efecto de recubrimientos sobre la postcosecha y la evolucion del color del zumo de la fruta del naranjo - Mataerano, W.=700 1 Valera, A.; Zambrano, J.; Maffei, M.; Torres, C.
(Es, En)
ilus., 19 ref.
Keywords: CITRUS SINENSIS; PRESERVACION; CERAS; CAROTENOIDES; CALIDAD; FENOLOGIA; POSTCOSECHA; VENEZUELA; AGRONOMIA TROPICAL